Isolation and Identification and Antibiotic Sensitivity of Bacterial Caused that Urinary Tract infection in Female - Obaid, khmaeel; Saad, Hanan; Hassan, Roaa (Medical Science Journal for Advance Research, 2024)
Background: The present study aimed to investigate 117 patients by medical signs of UTI referred to Al-Haidariya General Clinic, Al-Sadr and Al-Hakim Hospital in Al Najaf Governorate. The age group for women choice to (16-45years). Clean- midstream urine of the patients was together in the sterilized tube (3-5 ml), directly transmitted to the research laboratory). depended on the time of life distribution of the women in UTI. The age groups of (26 – 35 ages) that higher record with infection of UTI to n=39 (51.31%). E.Coli and Klebsiella pneumoniae isolates were the highest recorded infection in UTI with 33 (42.30 %) ,17 (21.79 % ).The main bacterial types isolated were identified according to cultural, morphological, microscopic report and bio chemical tests. The resistant of bacteria to different type of antibiotic, Ceftriaxone, Amoxicillin and Tetracycline is the most sensitive antibiotic to E. coli and Klebsiella pneumoniae this is related to the fact that tetracycline is active against both gram-positive and gram-negative bacteria. Conclusion: Urinary tract infection (UTI) is one of the record prevalence contagions productions in public health practice.